PASANG SURUT KEBEBASAN PERS DI INDONESIA - Satrio Saptohadi (Jurnal Dinamika Hukum, 2011)
In the New Order of the press regulated by Law No. 11 Year 1966, Law No. 4 Year 1967 and Law no. 21 Year 1982 which is a product of the repressive Soeharto regime, whereas in the era of reform after the resignation of Suharto's life enacted press Law No. 40 Year 1999 about the Press is full of euphoria. During the New Order's authoritarian press system produces under the guide of Pancasila press system that is free press and responsible, to the effect of press freedom in a way that is very restrained by bridle and thrown into prison their anti-government . In the Reform era of the press leading up to the liberal press system that is with the euphoria of freedom that went too far because there is no regulation of the repressive provisions. Key words : New order, the reform era and freedom of the press.